Temperamental and Personality Traits as Factors Related to Changes in Health Behaviors and Quality of Life in Patients With Metabolic Syndrome in Poland - Burnos, Agnieszka; Skrobowski, Andrzej (Frontiers in Psychology, 2021)
Lifestyle changes in diet and physical activity are necessary for managing metabolic syndrome. The aim of this longitudinal study was to examine temperamental and personality traits as moderators of lifestyle changes prompted by motivational intervention. The sample consisted of 50 patients aged 22–65years (M=45.26; SD=9.79) who fulfilled the diagnostic criteria for metabolic syndrome and were undergoing treatment at the Military Institute of Medicine in Warsaw. There were two measurements: an initial measurement and a second 15months after motivational counseling. Each patient completed the questionnaires: Formal Characteristics of Behavior – Temperament Inventory, NEO Five Factor Inventory, Inventory of Health Behavior, and Short Form Survey SF-36. Body Mass Index (BMI), Fat Mass, Fat-free Mass, Intracellular Water, and Basal Metabolic Rate (BMR) were also measured. Data were analyzed using dependent samples t-tests to detect the changes in consecutive measurements, the hierarchical regression analysis was used to investigate temperamental and personality traits as predictors of change, the cluster analysis was used to extract the subgroups of patients with distinct profiles of temperamental and personality traits, and the analysis of variance was used to analyze extracted profiles as potential moderators of change. Three subgroups were extracted using k-means clustering: patients with higher Neuroticism, Perseveration, and Emotional Reactivity; patients higher Extraversion, Briskness, Sensory Sensitivity, Endurance, Activity, and Conscientiousness; and patients with lower Perseveration. All patients improved significantly in terms of physical quality of life (QoL), health behaviors, BMI, BMR, and Fat-free Mass (p<0.05). Regression analysis found that higher Sensory Sensitivity, lower Perseveration, and higher Agreeableness fostered positive change (p<0.05). Patients with higher Neuroticism, Perseveration, and Emotional Reactivity also improved in terms of their Emotional Quality of Life and Health Practices, reaching parity with other patients, which was verified on the basis of statistically significant interaction (p<0.05). The temperamental and personality trait profiles moderated the changes in health practices and emotional QoL. Motivational counseling was effective for patients diagnosed with metabolic syndrome in general, but patients with higher Neuroticism, Perseveration, and Emotional Reactivity benefited even more, as they were in poorer psychological condition before the motivational intervention.